2012
DOI: 10.1242/jcs.097709
|View full text |Cite
|
Sign up to set email alerts
|

Latent process genes for cell differentiation are common decoders of neurite extension length

Abstract: SummaryA latent process involving signal transduction and gene expression is needed as a preparation step for cellular function. We previously found that nerve growth factor (NGF)-induced cell differentiation has a latent process, which is dependent on ERK activity and gene expression and required for subsequent neurite extension. A latent process can be considered as a preparation step that decodes extracellular stimulus information into cellular functions; however, molecular mechanisms of this process remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 50 publications
3
41
1
Order By: Relevance
“…The fact that multiple transduction pathways promote serpinb1a expression suggests that this gene could be involved in several cellular functions. Nevertheless, investigations achieved by using siRNA revealed that in contrast to what has recently been reported by Watanabe and collaborators (Watanabe et al 2012), in our hands serpinb1a inhibition with two different siRNA does not affect the ability of PACAP or NGF to promote neuritogenesis, induce growth arrest, or increase cell size. In contrast, it appeared that blockade of serpinb1a expression suppressed the ability of PACAP and NGF to inhibit caspases-3/7 activity.…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that multiple transduction pathways promote serpinb1a expression suggests that this gene could be involved in several cellular functions. Nevertheless, investigations achieved by using siRNA revealed that in contrast to what has recently been reported by Watanabe and collaborators (Watanabe et al 2012), in our hands serpinb1a inhibition with two different siRNA does not affect the ability of PACAP or NGF to promote neuritogenesis, induce growth arrest, or increase cell size. In contrast, it appeared that blockade of serpinb1a expression suppressed the ability of PACAP and NGF to inhibit caspases-3/7 activity.…”
Section: Discussioncontrasting
confidence: 99%
“…In cells capable of neuronal differentiation, such as PC12 cell, stimulation with NGF initiates a signal cascade that culminates in the transcriptional activation/repression of targets, as well as posttranslational modification of the activity for already present proteins (Watanabe et al 2012). According to our results, the overexpression of miR-183 and/or miR-96 in PC12 cells possibly downregulates genes induced by NGF stimulation necessary for neuronal differentiation.…”
Section: Mir183/96 Contribute To Pcc/pgl Tumorigenesis By Interferingsupporting
confidence: 55%
“…U0126 was developed as an inhibitor of MEK1/2 but has also been shown to inhibit MAPK7 [24]. Moreover, it was previously reported that U0126 suppresses upregulation of DCLK1 in response to NGF stimulation in PC12 cells [25] and a search of the NCBI gene expression omnibus database produced multiple datasets demonstrating significant DCLK1 downregulation following U0126 inhibition in colon cancer cell lines (Figure  4D & Additional file 1: Figure S2F) [26,27]. As predicted, DCLK1 mRNA levels were decreased after 10 μM U0126 treatment (Figure  4E).…”
Section: Resultsmentioning
confidence: 99%